(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
In recent years, international arbitration has emerged as an indispensable method for resolving disputes that include multiple countries because it provides impartiality, efficiency, and finality. In 1996, India passed the Arbitration and Conciliation Act, which is based on the UNCITRAL Model Law, in order to bring its legal system in line with international norms, acknowledging the significance of arbitration in today’s globalised economy. To make it easier to recognise and enforce foreign arbitral rulings, the Act combines provisions of the New York Convention (1958) and the Geneva Convention (1927). Judicial meddling, delays, an overly broad interpretation of the "public policy" exception, and a lack of institutional support are some of the problems that enforcement in India faces, despite the solid legislative basis. But there has been a trend in the judiciary towards a more enforcement-oriented stance, with landmark decisions in cases like BALCO, Shri Lal Mahal, and Vijay Karia bolstering international standards. Efficiency, impartiality, and institutionalisation were further fortified by legislative revisions in 2019, and 2021. This study delves into India’s achievements and ongoing challenges, coming to the conclusion that in order to establish India as a prominent arbitration centre, constant judicial restraint and strong institutional processes are crucial.